The Adventurous Four - Enid Blyton
Andy 14 takes pals visiting WW2 NE Scotland for an overnighter on Little Island. Small wiry redhead Tom 12 has cheerful twin sisters 10, Zoe and Pippa, with "thick golden plaits and deep blue eyes." But a sudden storm shipwrecks their little sailboat on deserted islets - with a cave of food supplies, a cove of submarines, and a seaplane of foreigners. The resourceful gang cope with discovery and danger. Lively brisk sketches bring the wind, waves, cliffs, and struggling sailors to life. The first fast moving appealing escapade with resourceful brave Adventurous Four.